2006
DOI: 10.1111/j.1538-7836.2006.01815.x
|View full text |Cite
|
Sign up to set email alerts
|

Urgent reversal of warfarin with prothrombin complex concentrate

Abstract: Summary. Background: When life-threatening bleeding occurs in patients on warfarin, timely reversal becomes imperative. In the USA, warfarin effect is commonly reversed with fresh frozen plasma (FFP). The use of FFP is complicated by delays in correction, volume overload and often, inadequate correction. Objective: Evaluate the feasibility and efficacy of a protocol for rapid administration of prothrombin complex concentrate (PCC) in the setting of the urgent need for reversal of warfarin. Methods/patients: We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
109
2
4

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 160 publications
(123 citation statements)
references
References 13 publications
8
109
2
4
Order By: Relevance
“…There were, however, seven thrombotic complications (that is, 1.5% of patients experienced a thrombotic event). Four of these, two deep vein thromboses and two non-ST elevation myocardial infarctions which were identified in a retrospective review of 58 patients, were not attributed to PCC therapy [15]. Two thrombotic strokes occurred in patients with extensive co-morbidities [16].…”
Section: Thrombotic Complications With Pccsmentioning
confidence: 99%
“…There were, however, seven thrombotic complications (that is, 1.5% of patients experienced a thrombotic event). Four of these, two deep vein thromboses and two non-ST elevation myocardial infarctions which were identified in a retrospective review of 58 patients, were not attributed to PCC therapy [15]. Two thrombotic strokes occurred in patients with extensive co-morbidities [16].…”
Section: Thrombotic Complications With Pccsmentioning
confidence: 99%
“…42 In general, 10 to 15 cc/kg FFP is used. 43 Timing rather than dosage seems to be more important for a better clinical outcome.…”
Section: Fresh Frozen Plasma (Ffp)mentioning
confidence: 99%
“…44,46 Therefore, a PCC dose of 25 to 59 U/kg has been used in life-threatening bleeding, resulting in a decrease in the median INR from 3.8 to 1.3 immediately after administration. 42 PCCs should always be given with vitamin K. Thrombotic events have been described with the infusion of PCCs, but no clear guidelines have been published. 42 A recent study from the Mayo Clinic showed that many experts suggest its use in the urgent condition of warfarin-associated ICH.…”
Section: Fresh Frozen Plasma (Ffp)mentioning
confidence: 99%
See 2 more Smart Citations